Miejsce analogów prostaglandyn w farmakoterapii jaskry – stan obecny - Wierzbowska, Joanna; Rękas, Marek; Malawko, Daria (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Therapy with prostaglandin analogues (PGA), a novel class of intraocular-lowering medications, represents a safe and very effective pharmacologic method of treating patients with glaucoma and ocular hypertension. The convince dosing regimen, once-daily, higher efficacy and higher systemic safety profile seen with PGA compared with betablockers caused that these agents have been approved by regulatory bodies for both the first-line and adjunctive therapy. Short, retrospective analysis of the medical treatment of glaucoma in the Ophthalmology Clinic of Military Health Service Institute in Warsaw, in 2003-2004, was presented.